Identifying and Quantifying the Role of Inflammation in Pain Reduction for Patients With Psoriatic Arthritis Treated With Tofacitinib: A Mediation Analysis - Kurt de Vlam; Philip J. Mease; Andrew G. Bushmakin; Roy Fleischmann; Alexis Ogdie; Valderílio Feijó Azevedo; Joseph F. Merola; John Woolcott; Joseph C. Cappelleri; Lara Fallon; Peter C. Taylor (2022)
Pain is a multidimensional factor and core domain of psoriatic arthritis (PsA). This analysis aimed to quantify the role of potential inflammation-associated outcomes on pain reduction in patients with PsA receiving tofacitinib, using mediation modeling. Pooled data were from two phase 3 studies (OPAL Broaden and OPAL Beyond) of patients with active PsA treated with tofacitinib 5 mg twice daily or placebo. Mediation modeling was utilized to quantify the indirect effects (via Itch Severity Item [ISI], C-reactive protein [CRP] levels, swollen joint count [SJC], Psoriasis Area and Severity Index [PASI], and enthesitis [using Leeds Enthesitis Index]) and direct effects (representing all other factors) of tofacitinib treatment on pain improvement. The initial model showed that tofacitinib treatment affects pain, primarily indirectly, via ISI, CRP, SJC, PASI, and enthesitis (overall 84.0%; P = 0.0009), with 16.0% (P = 0.5274) attributable to the direct effect. The model was respecified to exclude SJC and PASI. Analysis of the final model revealed that 29.5% (P = 0.0579) of tofacitinib treatment effect on pain was attributable to the direct effect, and 70.5% (P < 0.0001) was attributable to the indirect effect. ISI, CRP, and enthesitis mediated 37.4% (P = 0.0002), 15.3% (P = 0.0107), and 17.8% (P = 0.0157) of the tofacitinib treatment effect on pain, respectively. The majority of the effect of tofacitinib on pain was collectively mediated by itch, CRP, and enthesitis, with itch being the primary mediator of treatment effect. Trial Registration: NCT01877668, NCT01882439.